Analysis the Effect of Total Assets Profitability and Leverage on Audit Delay (Study on Companies Listed on Indonesia Stock Exchange From 2018-2020) - Angeline Han (NAROTAMA UNIVERSITY, Indonesia, 2022)
One of financial statement characteristic is puncuality. Information from financial statements that have been not reported on time can cause the value of the information to be reduced in decision making as a basis for determining future actions. Timeliness of the submission of financial statements is very important for companies and users of financial statements, the timeliness of companies in submitting financial statements also depends on the timeliness of auditors in completing their audit work. The long audit process from the deadline for submitting financial statements is called audit delay. This study aims to analyze the effect of total assets, profitability, and leverage on audit delay. The study was conducted on 58 companies listed on the Indonesia Stock Exchange from 2018-2020 and the data were taken form of annual financial reports published by each company. This study uses quantitative methods and the data analysis technique used is multiple linear regression analysis. The results of this study indicate that total assets and leverage have an effect on audit delay, while profitability has no effect on audit delay. And, simultaneously total assets, profitability and leverage have an effect on audit delay.